2005
DOI: 10.1264/jsme2.20.178
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Activities of Surface Associated Bacteria Isolated from the Marine Sponge Pseudoceratina purpurea

Abstract: The effects of four strains of Gram positive bacteria (PS2, PS9, PS11, and PS79) isolated from the sponge Pseudoceratina pupurea on the growth of a set of fouling bacteria and standard strains of genera Vibrio-Photobacterium were examined. Using a paper disc diffusion method, 4 sponge isolates were found to have inhibitory activity against 4 of 12 isolates of the fouling bacteria. All of the four bacterial supernatants also showed inhibitory activity against Vibrio alginolyticus and V. fischeri, while sponge e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
(30 reference statements)
0
7
0
2
Order By: Relevance
“…from seagrass Enhalus acoroides inhibited the growth of biofilm-forming bacteria. A study by Kanagasabhapathyt et al (2005) demonstrated the inhibition of growth of fouling bacteria by sponge Pseudoceratina purpure-associated bacterium Virgibacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…from seagrass Enhalus acoroides inhibited the growth of biofilm-forming bacteria. A study by Kanagasabhapathyt et al (2005) demonstrated the inhibition of growth of fouling bacteria by sponge Pseudoceratina purpure-associated bacterium Virgibacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Simbiosis yang terjadi antara bakteri dengan spon laut menyebabkan invertebrata laut ini memiliki potensi antibakteri yang lebih besar dibandingkan dengan organisme darat dan laut lainnya [6].…”
Section: Pendahuluanunclassified
“…The role of sponge-associated microorganisms in the synthesis of compounds of biological interest is a subject of scientific debate, as in some cases these bacteria are reported to produce bioactive metabolites (Imhoff and Stöhr 2003). Antimicrobial activity has been reported for the bacteria associated with marine sponges collected from diverse areas viz., Antarctic region (Mangano et al, 2009), temperate (Chellossi et al, 2004 and tropical coastal waters (Thakur and Anil 2000, Kanagasabapathy et al, 2005, Anand et al, 2006. The present investigation aims at characterizing the cultivable heterotrophic fraction of surface-associated bacteria in a marine sponge, Stylissa sp from Andaman, India and investigating their antimicrobial properties against selected human, animal and plant pathogens.…”
Section: Introductionmentioning
confidence: 99%